Laminar flow field in a viscous liquid impinging jet confined by inclined plane walls - A. S. Cavadas (2012)
An experimental and numerical investigation was carried out to characterize the isothermal laminar flow of a liquid impinging jet confined by inclined plane walls and emanating from a rectangular duct, where the flow was allowed to become fully-developed. The rectangular duct has an aspect ratio of 13, the plane walls opposite to the impinging jet have an inclination of 12 degrees and the nozzle-to-plate distance (D) is very short, D/H = 0.8. The presence of the impact plate is felt upstream the nozzle, inside the rectangular duct, up to x/H = -0.4. The flow in the cell is symmetric relative to the x-y and x-z center planes and near the inclined walls the flow separates for Reynolds numbers higher than 208, except close to the side walls where the flow remains attached. The length of the separated flow region, L-R, measured along the inclined wall, is constant in the central portion of the channel with L-R/H = 0.35 for Re = 275 and dropping to zero before reaching the side walls. The recirculation length increases with the Reynolds number and with the thickness of the outlet channel. There is a three-dimensional effect associated with the finite slenderness of the geometry. It consists of spiraling secondary motions away from the central symmetry plane and toward the side walls, where the fluid merges with the main flow creating a local wall jet, as is discussed in detail.